Hungarian Monitoring, 13 May 1988 . [Magyar rádiófigyelő], 1988. május 13 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Powell informs US Senate of Geneva agreement - Gromyko in Romania - Warsaw Pact military council meeting in Sofia Domestic Affairs: - Péter Várkonyi's account of foreign ministers' meeting in Berlin - György Fejti talks at the Technical University on the importance of Party meetings - “Green corridor” border crossings to be introduced at Sopron and Hegyeshalom -Pilot census in Nógrád - Dangerous waste disposal furnace at Nagykanizsa Economy: - First quarterly imports down - 30 countries at the spring Budapest International Trade Fair Külpolitika - Powell tájékoztatja a Szenátust a genfi megállapodásokról - Gromiko Romániában - A VSZ katonai tanácsának szófiai ülése Belpolitika: - Várkonyi Péter beszámolója a berlini külügyminiszteri találkozóról - Fejti György a Műegyetemen beszél a pártértekezlet jelentőségéről - Sopronnál és Hegyeshalomnál "zöld folyosó" nevű határátlépést vezetnek be - Kísérleti népszámlálás Nógrádban - Veszélyes hulladékégető Nagykanizsán Gazdaság: - Csökkent az első negyedévi import - 30 ország a tavaszi BNV-n